RESEARCH AND DEVELOPMENT OF GENETIC ENGINEERING IN MEDICINE AND AGRICULTURE IN THE UNITED STATES OF AMERICA - Ha, Nguyen Hai; Bich Hang, Pham Le; Hai, Nong Van; Thu Hien, Le Thi (Vietnam Journal of Biotechnology, 2018)
The status of research, development and application of genetic technology in the US has been reflected through efforts and accomplishments in numerous fields including research, medicine, industrial biotechnology and agriculture in the past decades. In the area of medicine, the field of therapeutic purposes on human is the pioneer, in which gene therapy is attempted to carry out in various clinical trials. Diagnostic applications of human diseases which focus primarily on infectious diseases, cancer, pharmacogenomics and screening for inherited diseases by using molecular techniques related to PCR, next generation sequencing are followed. In addition, preparatory studies on human cells utilizing CRISPR/Cas9 genome editing technology have been undertaken in hopes of finding new treatments for cancer and rare form of eye disorder. In the field of agriculture, many large companies in the US have been developing varieties of genetically modified crops with traits of herbicide tolerance, insect resistance, drought resistance and nutrition enhancement. Among the biotech crops, proportion of planted acres of genetically engineered soybean, corn and cotton were increased rapidly and forecasted to expand in the coming years. Studies on generating genetically modified animals and fisheries have also been concentrated in order to not only resist diseases, enhance nutrition, but also provide pharmaceutical compounds. Application of new gene editing techniques such as CRISPR/Cas9 on plants and animals help biotech products have more opportunities to be approved for commercial sale in the US market. In general, although the research and application of genetic engineering in the US has outstripped worldwide, numerous obstacles are still encountered due to serious ethical regulations and controversy regarding to human health and environment. The US government continues to establish suitable policies and invest in science and technology to improve the quality of human life.